2020
DOI: 10.20517/2574-1225.2020.57
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal transection in robotic liver resection: results of 70 resections using the Vessel Sealer

Abstract: Aim: There is no standard technique for transection of the hepatic parenchyma during robotic liver resection. The aim of this study was to describe the outcomes of robotic liver resections using the Vessel Sealer for parenchymal transection. Methods: This is a post hoc analysis of a prospective database. All consecutive patients who underwent robotic liver resection in the Regional Academic Cancer Centre, Utrecht, Netherlands, between August 2015 and January 2019 were included. Results: A total of 70 robotic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Nota et al could demonstrate that the Vessel Sealer is generally employable for parenchymal bile ducts, portal branches, and veins but a stapler and/or hemolocks are used for inflow/outflow pedicles, major veins, or when larger vascular structures are encountered that are clearly beyond a size that could easily be sealed with a margin within the length of the sealer’s surface at 90 degrees. The authors therefore conclude that the Vessel Sealer is appropriate to seal most vascular structures encountered within the parenchyma of the liver segments [ 71 ].…”
Section: Technical and Surgical Aspectsmentioning
confidence: 99%
“…Nota et al could demonstrate that the Vessel Sealer is generally employable for parenchymal bile ducts, portal branches, and veins but a stapler and/or hemolocks are used for inflow/outflow pedicles, major veins, or when larger vascular structures are encountered that are clearly beyond a size that could easily be sealed with a margin within the length of the sealer’s surface at 90 degrees. The authors therefore conclude that the Vessel Sealer is appropriate to seal most vascular structures encountered within the parenchyma of the liver segments [ 71 ].…”
Section: Technical and Surgical Aspectsmentioning
confidence: 99%
“…However, outcomes were not discussed for different transection techniques. Nota et al [ 2 ] have used VS exclusively in their series of 70 liver resections. Among them, only 10 (14%) were major hepatectomies with a conversion rate of 7%.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, only 10 (14%) were major hepatectomies with a conversion rate of 7%. They reported that 14% suffered from a major complication [ 2 ]. They did not encounter any technical difficulty or instrument failure when using the VS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Despite these advancements, liver parenchymal transection during robotic liver resection (RLR) remains a significant challenge, mainly because of a limited range of robotic instruments specifically designed for liver parenchymal transection, and the lack of a standardised technique. [3][4][5] Various methods have been explored, such as saline-linked monopolar cautery scissors, 3 the saline-linked bipolar clamp-crush technique, 4 cavitron ultrasonic surgical aspirator (CUSA; Integra Life Sciences, Tullamore, Ireland), 6 ultrasonic coagulation and incision devices (Harmonic; Intuitive Surgical, Sunnyvale, CA, USA), 7 the radiofrequency energy device (Vessel Sealer; Intuitive Surgical, Sunnyvale, CA, USA), 8 and waterjet (Erbejet; Erbe Elektromedizin GmbH, Tuebingen, Germany), 9 each presenting its own set of benefits and limitations. For example, the robotic Harmonic scalpel lacks an pathological data, and postoperative outcomes were collected from the patient's electronic medical records.…”
Section: Introductionmentioning
confidence: 99%